2023
DOI: 10.1002/aisy.202300173
|View full text |Cite
|
Sign up to set email alerts
|

Reprogrammable Magnetic Soft Robots Based on Low Melting Alloys

Abstract: Magnetic soft robots featuring untethered actuation and high mechanical compliance have promising applications ranging from bionics to biomedicine. However, their fixed magnetization profiles pose a challenge for adaptive shape transformation in unpredictable environments and dynamic tasks. Herein, a reprogrammable magnetic soft composite is reported by encapsulating magnetic neodymium–iron–boron microparticles with low melting alloy (LMA) and embedding them into the elastomer. Utilizing the phase transition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…3D(ii)). 73,77 The driving force, F m , and driving torque, Γ m , acting on such elastomers can be given by 78 F m = μ 0 V ( M r ·∇) H Γ m = μ 0 V ( M r × H )where M r is the remanent magnetization and V is the volume of the magnetic elastomers.…”
Section: Actuation Mechanismsmentioning
confidence: 99%
“…3D(ii)). 73,77 The driving force, F m , and driving torque, Γ m , acting on such elastomers can be given by 78 F m = μ 0 V ( M r ·∇) H Γ m = μ 0 V ( M r × H )where M r is the remanent magnetization and V is the volume of the magnetic elastomers.…”
Section: Actuation Mechanismsmentioning
confidence: 99%
“…Xueqi Li et al used cellulose nanofibers through a papermaking process, added sodium alginate and BaFe 12 O 19 particles to synthesize M-films with good foldability, origami, and magnetism, and constructed a multimodal magnetic gripper robot with the functions of programmable movement, grasping and transporting goods, and wireless operation through origami magnetization [ 26 ]. Gangsheng Chen et al constructed a material with multiple programmable temperatures, as the composition of the low-melting alloy (LMA) changes by encapsulating magnetic NdFeB particles with the LMA and embedding them in an elastomer, and the material can be used to fabricate bio-inspired tracks with multimodal motions, reconfigurable robotic grippers capable of adapting to grasping, and reconfigurable electronic circuits [ 27 ]. Zhaoxin Li et al reported a novel multilayer for patterning magnetic nanoparticles in an ultraviolet (UV) cured polymer matrix 3D printing technique, which can be used to achieve shape changes in the robot, including grasping, rolling, swimming, and walking, induced by the global actuation field by programming heterogeneous magnetization within discrete multilayer robotic segments [ 28 ].…”
Section: Introductionmentioning
confidence: 99%